2022
DOI: 10.3389/fneur.2022.866424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Prolong Life With Nine Turn Method (Yan Nian Jiu Zhuan) Qigong on Brain Functional Changes in Patients With Chronic Fatigue Syndrome in Terms of Fatigue and Quality of Life

Abstract: BackgroundChronic fatigue syndrome (CFS) is characterized by persistent fatigue, which often leads to physical and psychological damage. The Prolong Life with Nine Turn method (PLWNT) Qigong is considered as one of the complementary treatments for improving symptoms in patients with CFS. In this study, we used functional magnetic resonance imaging (fMRI) to explore the effects of PLWNT intervention on the subjects with CFS.MethodsThirty four CFS patients were randomly divided into PLWNT group and cognitive beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Since that time, multiple studies have confirmed these findings in young [64][65][66], middle-aged [67,68], and older adults [69,70]. There is preliminary evidence that Qigong may have similar effects [71,72].…”
Section: Introductionmentioning
confidence: 82%
“…Since that time, multiple studies have confirmed these findings in young [64][65][66], middle-aged [67,68], and older adults [69,70]. There is preliminary evidence that Qigong may have similar effects [71,72].…”
Section: Introductionmentioning
confidence: 82%
“…Patients with insomnia disorder demonstrate decreased thalamic connectivity with the left amygdala, parahippocampal gyrus, putamen, pallidum, and hippocampus across wakefulness [ 43 ]. Previous studies have shown that qigong can affect the brain response [ 22 , 44 - 46 ]. This trial strives to bridge the existing knowledge gap by combining fMRI, which investigates arousal responses spatially within the brain, with wrist actigraphy, enabling the temporal monitoring of arousal status.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations into insomnia treatment have primarily centered on enhancing sleep quality but have often overlooked the assessment of daytime functioning. In contrast, our previous research findings suggested that qigong exhibits efficacy both in ameliorating sleep quality and in enhancing daytime functioning [ 22 ].…”
Section: Introductionmentioning
confidence: 86%
“…Since that time, multiple studies have confirmed these findings in young [ 64 – 66 ], middle-aged [ 67 , 68 ], and older adults [ 69 , 70 ]. There is preliminary evidence that Qigong may have similar effects [ 71 , 72 ].…”
Section: Introductionmentioning
confidence: 99%